Animals and society : an introduction to human-animal studies. - DeMello, Margo (New York : Columbia University Press, 2021)
Human-animal studies is an interdisciplinary field that explores the spaces that animals occupy in human social and cultural worlds. Margo DeMello provides a broad overview of this rapidly growing field. This second edition is fully updated and expanded throughout, enhancing the book's relevance for student and activist readers alike.
13. Human Oppression and Animal Suffering -- Part IV: Imagining Animals: Animals in Human Thought -- 14. Animals in Symbol and Art -- 15. Animals in Religion and Folklore -- 16. Animals in Literature and Film -- Part V: Knowing and Relating to Animals: Animal Behavior and Animal Ethics -- 17. Animal Behavior Studies and Ethology -- 18. The Moral Status of Animals -- 19. The Animal Protection Movement -- 20. The Future of the Human-Animal Relationship -- Bibliography -- Index
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Animals and civilization -- History; Human-animal relationships -- History; Human-animal relationships; Animaux et civilisation -- Histoire; Relations homme-animal -- Histoire; Relations homme-animal.; NATURE / Animal Rights; Animals and civilization; Human-animal relationships; Human-Animal Studies; animal cruelty; animal ethics; animals and society; philosophy of animals; veganism; History